Female owners versus female managers: Who is better at introducing innovations? - Dirk Dohse; Rajeev K. Goel; Michael A. Nelson (Kiel Institute for the World Economy (IfW), 2017)
This paper uses firm-level survey responses across more than 100 emerging and developing countries to examine whether female managers or female owners of firms were better at bringing innovations to the market. Employing a range of firm-specific and country-specific controls, the econometric results show that female owners of firms, rather than female managers, were more likely to introduce innovations. As expected, innovations resulted from firms engaging in R&D. Larger and older firms reinforced these tendencies; however, sole proprietorships had the opposite effect. The presence of an informal sector and finance availability constraints actually spurred innovation. Finally, the economy-wide effects of greater economic freedom and stronger patent protections were positive, while greater economic prosperity somewhat led to complacency.
Keywords: O32; O33; O57; J16; 330; innovation; female; owners; managers; patent protection; R&D; firm size; sole proprietorship